Development of Cook Based On the Fridge System - Koh, Kar Men; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2022)
Cook based on the fridge system is a recipe discovery system that offered a personalized menu of recipes you can make using the ingredients you have at home. This can help users save time searching for recipes on the Internet. In addition, users can avoid food waste for food that may not last long, such as vegetables and fruit. By using this method, users can gain benefits by not spending time looking for similar recipes on the Internet and recipe books containing the ingredients they have. This system can help users to list down the ingredients they need to buy in the shopping list part. Grocery store locator in the system can help users to spot the nearest grocery store or supermarket to purchase the ingredients.